2016
DOI: 10.4238/gmr.15026564
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity of Tunisian orange, Citrus sinensis (L.) Osbeck using microsatellite (SSR) markers

Abstract: ABSTRACT. Citrus are one of the most cultivated crops in the world. Economically, they are very important fruit trees in Tunisia. Little is known about the genetic diversity of the Tunisian Citrus germplasm. Exploring this diversity is a prerequisite for the identification and characterization of the local germplasm to circumvent and controlling genetic erosion caused by biotic and abiotic stress to aid its conservation and use. In the present study, we explored the genetic diversity of 20 Tunisian orange cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Indeed, this orange was believed to be the same as Maltaise demi-sanguine cultivar, however, our results show that they are genetically different and they share only 7 alleles from a total of 18. Those results are in agreement with the findings of Mahjbi et al (2016) where two Sakasli and two 'Maltaise demi-sanguine' cultivars where found to be genetically different while analyzed by SSR markers. With the use of this set of markers, we could identify cases of synonymy and homonymy or misidentification.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, this orange was believed to be the same as Maltaise demi-sanguine cultivar, however, our results show that they are genetically different and they share only 7 alleles from a total of 18. Those results are in agreement with the findings of Mahjbi et al (2016) where two Sakasli and two 'Maltaise demi-sanguine' cultivars where found to be genetically different while analyzed by SSR markers. With the use of this set of markers, we could identify cases of synonymy and homonymy or misidentification.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to dominant markers, SSR markers are co-dominant, highly reproducible, multi-allelic, and widely used in plant sciences (Hajmansoor et al, 2013) for germplasm characterization (Varshney et al, 2005;Peng et al, 2015;Queiroz et al, 2015), identification of genetic diversity (Gurcan et al, 2015;Jo et al, 2015;Mahjbi et al, 2016;Mornkham et al, 2016;Neiva et al, 2016), germplasm fingerprinting (Zhang et al, 2015), and integration of genetic linkage maps (Lai et al, 2013). For C. sinensis, SSR markers have been widely used to identify germplasm genetic diversity (Taniguchi et al, 2014), construction of linkage maps (Tan et al, 2013) and DNA-fingerprinting (Ujihara et al, 2009;Ma et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained H E values of Indian jujube were closer to other tropical fruit trees such as mango cultivars [ 27 ], wax apple [ 26 ] and camu-camu [ 57 ], but much lower compared to Japanese plum cultivars [ 58 ], apple cultivars [ 59 ], Tunisian orange [ 60 ], Asian pear [ 61 ] and Chinese jujube [ 62 ]. These fruit cultivars have strong self-incompatibility [ 62 , 63 , 64 ] including Indian jujube [ 7 ].…”
Section: Discussionmentioning
confidence: 75%